X(1870) and η2(1870): Which Can Be Assigned as a Hybrid State? - Bing Chen; Ke-Wei Wei; Ailin Zhang (Advances in High Energy Physics)
The mass spectrum and strong decays of the X(1870) and η2(1870) are analyzed. Our results indicate that X(1870) and η2(1870) are the two different resonances. The narrower X(1870) seems likely a good hybrid candidate. We support the η2(1870) as the η2(21D2) quarkonium. We suggest to search the isospin partner of X(1870) in the channels of J/ψ⟶ρf0980π and J/ψ⟶ρb11235π in the future. The latter channel is very important for testing the hybrid scenario.